Hierarchically-structured metalloprotein composite coatings biofabricated from co-existing condensed liquid phases - Franziska Jehle (Nature Portfolio, 2020)
The mussel byssus cuticle is a wear-resistant and extensible metalloprotein composite. Here, the authors probed the cuticle nanostructure and composition before, during and after fabrication revealing a crucial role of metal-binding proteins that self-organize via liquid-liquid phase separation.